Effect of storage conditions on rancidity and antioxidant activity of gac oil compared with healthy oils - Montip Chamchong; Darun Waeruwanaruk; Chanikarn Guntornkun; Tania Alam (Agriculture and Natural Resources, 2021)
The kinetic changes were studied of the chemical attributes (oxidative and hydrolytic rancidity, lycopene, beta-carotene, antioxidant capacity) of gac oil during storage with and without limited oxygen at different temperatures. The results were compared with those of other healthy oils (virgin olive, virgin rice bran, virgin camellia tea seed) stored under the same conditions. Samples (each 7 mL) of the oils were stored in 10 mL open-capped and closed-capped amber glass bottles and kept at four different storage temperatures (5°C, 25°C, 40°C, 60°C) for 1 mth. Before being kept in storage, the gac oil had the highest antioxidant capacity (mean ± SD; 143.53 ± 10.62 mg ascorbic acid equivalents (AAE)/g oil) and after storage at 40–60°C, its degradation rate of antioxidant capacity was the lowest. The antioxidant capacity of the gac oil remained the highest in the range 46.75 ± 1.05 mg AAE/g oil to 54.06 ± 0.29 mg AAE/g oil despite decolorization from dark-red to an orange-yellow color at these storage temperatures (40–60°C). The rate constant of reaction regarding hydrolytic rancidity for rice bran oil increased more rapidly than for the other oils when the storage temperature increased.